The state of carotid artery wall in hypertensive patients with gout based on the study of inflammatory markers - H. P. Kuzmina; O. M. Lazarenko (Zaporožskij Medicinskij Žurnal)
The aim. To analyze the frequency of atherosclerotic lesions of the carotid arteries and association with the lipid metabolism and inflammatory markers in hypertensive patients with gout.